2022
DOI: 10.3390/ijms232012363
|View full text |Cite
|
Sign up to set email alerts
|

Novel Class of Proteasome Inhibitors: In Silico and In Vitro Evaluation of Diverse Chloro(trifluoromethyl)aziridines

Abstract: The ubiquitin-proteasome pathway (UPP) is the major proteolytic system in the cytosol and nucleus of all eukaryotic cells. The role of proteasome inhibitors (PIs) as critical agents for regulating cancer cell death has been established. Aziridine derivatives are well-known alkylating agents employed against cancer. However, to the best of our knowledge, aziridine derivatives showing inhibitory activity towards proteasome have never been described before. Herein we report a new class of selective and nonPIs bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…[14][15][16] Taking into account the relevant reactivity of conjugated double bonds towards nucleophiles, we decided to exploit the cinnamic ester moiety for the design of novel peptide-based SARS-CoV-2 M pro inhibitors, in the context of our ongoing research activity aimed at the identification of protease inhibitors. [17][18][19] In this study we present a panel of 11 unprecedented p-aminocinnamic ethyl esters derivatives, which are joined to a L-Phe residue variously decorated at the N-terminus with carbamate, urea and indole-bearing amide recognition functionalities. The enzymatic assays against viral proteases revealed that these compounds are selective inhibitors of SARS-CoV-2 M pro with IC 50 values in the lower micromolar range, in comparison to that of PL pro (no inhibition at 20 μM).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Taking into account the relevant reactivity of conjugated double bonds towards nucleophiles, we decided to exploit the cinnamic ester moiety for the design of novel peptide-based SARS-CoV-2 M pro inhibitors, in the context of our ongoing research activity aimed at the identification of protease inhibitors. [17][18][19] In this study we present a panel of 11 unprecedented p-aminocinnamic ethyl esters derivatives, which are joined to a L-Phe residue variously decorated at the N-terminus with carbamate, urea and indole-bearing amide recognition functionalities. The enzymatic assays against viral proteases revealed that these compounds are selective inhibitors of SARS-CoV-2 M pro with IC 50 values in the lower micromolar range, in comparison to that of PL pro (no inhibition at 20 μM).…”
Section: Introductionmentioning
confidence: 99%
“…2). 105 Other anticancer aziridine bearing molecules were reported by Cheke et al as inhibitors of the stem cell growth factor receptor often known as the c-KIT kinase domain. This is one of the 20 subfamilies of human receptor tyrosine kinases (RTKs) which is one of the main studied targets to fight cancer.…”
Section: Aziridines Showing Activity Against Oncological Targetsmentioning
confidence: 99%
“…AMBER 14 force field was used for the simulation. [29] The MD simulations of the complexes were performed with the YASARA structure package according to our previously reported procedures. [46,47]…”
Section: Molecular Docking and Dynamicsmentioning
confidence: 99%
“…Considering the results achieved so far regarding the development of noncovalent PIs [ 28–31 ] and in agreement with preliminary docking studies, the inhibitory activity of a set of bis‐homologated chloromethyl(trifluoromethyl)aziridines (CMTMAs) was evaluated toward this anticancer target. [ 32 ]…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation